BIOLOGY OF BOMBAY DUCK, HARPODON NEHEREUS (HAM., 1822), FROM MUMBAI WATERS, INDIA - Balli, Johnson J.; Chakraborty, S. K.; Jaiswar, A. K. (Journal of Indian Fisheries Association, 2006)
Morphometric and meristic study of Harpodon nehereus (Hamilton, 1822) from Mumbai waters indicated that the specimens belonged to a homogenous population. Based on the meristic study, the fin formula can be written as B23_w D12_m P11_m V9, A13_15, Cm L40_ Length-weight study revealed an allometric relationship, presented as Log W = -3.1362 + 3.6059 Log L. The analysis of food and feeding habits revealed the species to be voracious, carnivorous and cannibalistic, feeding mainly on Acetes spp., juveniles of H. nehereus itself, prawns and Coilia dussumieri. The feeding intensity was found to be the maximum during September and November, and also in mature specimens which may be the preparation for the ensuing spawning activity. Reproductive biology indicated two peak spawning seasons in November and March. However, the species as a whole has prolonged breeding season and spawning occurs throughout the year. Average fecundity was estimated as 314 ova/g body weight of fish and the length at which 50% of female specimens mature (Lc50) was calculated as 255 mm. Keywords: Harpodon nehereus, morphometry, length-weight relationship, food and feeding habits, reproduction